Current understanding and challenges of solar-driven hydrogen generation using polymeric photocatalysts - Wang,Y; Vogel,A; Sachs,M; Sprick,RS; Wilbraham,L; Moniz,SJA; Godin,R; Zwijnenburg,MA; Durrant,JR; Cooper,AI; Tang,J (Nature Energy, 2019)
The use of hydrogen as a fuel, when generated from water using semiconductor photocatalysts and driven by sunlight, is a sustainable alternative to fossil fuels. Polymeric photocatalysts are based on Earth-abundant elements and have the advantage over their inorganic counterparts in that their electronic properties are easily tuneable through molecular engineering. Polymeric photocatalysts have developed rapidly over the past decade, resulting in the discovery of many active materials. However, our understanding of the key properties underlying their photoinitiated redox processes has not kept pace, and this impedes further progress to generate cost-competitive technologies. Here, we discuss state-of-the-art polymeric photocatalysts and our microscopic understanding of their activities. We conclude with a discussion of five outstanding challenges in this field: non-standardized reporting of activities, limited photochemical stability, insufficient knowledge of reaction mechanisms, balancing charge carrier lifetimes with catalysis timescales and the use of unsustainable sacrificial reagents.